Building Magritek: New Zealand’s magnetic resonance imaging company - Coy, Andrew (New Zealand Science Review, 2011)
​​Magritek is a technology company creating innovative products in the fields of Nuclear Magnetic Resonance and Magnetic Resonance Imaging. The initial technology and IP used in Magritek products was developed by research teams at both Massey University and Victoria University of Wellington.Magritek commenced in 2004 and is today profitable, cash flow positive, paying taxes and growing, with a particular focus on the oil and gas industry. The intellectual property and research underpinning the Magritek products comes from two decades of world leading magnetic resonance research carried out by director and founder Professor Sir Paul Callaghan and his team. Some of the challenges and opportunities that Magritek has worked through in generating a viable manufacturing and export driven business based in Wellington, New Zealand were presented at the conference.